Peripheral arterial disease has a strong impact on cardiovascular outcome in patients with acute coronary syndromes: from the START Antiplatelet registry. (15th March 2021) - Gresele, P.; Guglielmini, G.; Del Pinto, M.; Calabrò, P.; Pignatelli, P.; Patti, G.; Pengo, V.; Antonucci, E.; Cirillo, P.; Fierro, T.; Palareti, G.; Marcucci, R.; et al.
Abstract: Background: Peripheral arterial disease (PAD) was reported to increase the risk of new cardiovascular events in patients with acute coronary syndromes (ACS). However, most of the evidence comes from randomized clinical trials. We aimed to assess the impact of PAD on cardiovascular outcome and treatment decisions in ACS patients in a current real-life setting. Methods: START-ANTIPLATELET is a multicenter registry enrolling ACS patient. Baseline clinical characteristics and treatment at discharge were recorded and follow-up was repeated at 6-months and 1-year. PAD was defined as intermittent claudication and/or previous revascularization. Results: Among 1442 patients enrolled, 103 (7.1%) had PAD. PAD patients were older (71.8 ± 10.6vs66.2 ± 12.6 yrs., p < 0.0001), more frequently hypertensive (90.3vs68.6%, p < 0.0001), hypercholesterolemic (66vs52%, p = 0.037), diabetic (51.5vs24%, p = 0.0001), obese (28.2vs19.3%, p = 0.029) and with previous TIA (7.8vs2.8%, p = 0.005) or stroke (11.7vs3.1%, p< 0.0001). Clinical presentation and acute treatment were similar in non-PAD and PAD patients, but the latter were discharged significantly less frequently on dual antiplatelet therapy (DAPT) (68.9vs85%, p = 0.005). After a median follow-up time of 11.1 months, major cardio/cerebrovascular event-free survival [MACCE, including cardiovascular death, MI, TIA and stroke, target-vessel revascularization (TVR) and major arterial ischemic events] was significantly shorter (9.0vs11.2 months, p = 0.02; HR 3.2, 2.4–8.4) in PAD patients and net adverse cardiovascular events (NACE = MACCE plus major hemorrhages) were significantly more frequent (19.1%vs10.5%, p = 0.049). Conclusions: PAD identifies a subgroup of ACS patients at significantly increased cardiovascular risk, but these patients tend to be undertreated. Patients admitted for ACS should be screened for PAD and optimal medical therapy at discharge should be implemented. Highlights: Peripheral arterial disease represent a frequent comorbidity among ACS Patients. PAD patients have a worse risk factor profile and higher CV risk on follow-up. PAD patients tend to be undertreated at discharge. ACS patients should be investigated for PAD and optimal therapy should be applied.